System Dynamics Model and Policy Scenario Analyses on International Movements of Indonesian Scientists and Engineers - Inayati, Tutik; Mori, Shunsuke; Nuraeni, Shimaditya (The Asian Journal of Technology Management (AJTM), 2016)
Abstract. The necessity to face technology challenges in industrialization in Indonesia causes the current condition to be not preferable. Conditions in higher education which relates closely to the research and development in Indonesia trigger questions of what future holds in Indonesia’s technology development in the future. This paper looks back at the previous literatures on international movements of scientists and engineers abroad and proposes to apply a causal loop diagram model. This paper also analyzes the relationships based on Indonesia’s context and set a parameter for each variable. The relationships were checked through interview with representation from Indonesian research institutions and Ministry of Foreign Affairs. The result of this paper confirms that the diagram is able to symbolize the circumstances in Indonesia’s context. Second important finding is that based on simulation and policy scenarios implemented, the policy to increase the number of scholarships by the government is predicted as the most effective to all important parameters for future development in Indonesia in relation to education and technology development, which will eventually lead to economic development.Keywords:  Engineers, international students, policy scenarios, scientists, system dynamics